Compulsion and reactance: Why do some green consumers fail to follow through with planned environmental behaviors?. Issue 12 (10th August 2021) - Hinsch, Christian; Tang, Yihui (Elina); Lund, Donald J.
Abstract: Some green consumers fail to follow through with planned environmental behaviors (EB), despite claiming intent to do so. The current research draws on reactance theory to shed light on this paradox at the intersection of environmentalism, sustainability, and green marketing. Historically, individuals have been conceptualized dichotomously as either pro or antienvironmental. Mann questions this simplistic perspective and introduces the "Wizard" and "Prophet" as environmentalist archetypes. Wizards and Prophets both engage in EB, but Wizards perceive science and technology as potential solutions, whereas Prophets believe consumption reduction is the only answer. Building upon self‐discrepancy theory and using both qualitative and quantitative data, we find support for Mann's thesis that both environmentalist archetypes exist, and both have inclinations toward EB. Furthermore, these archetypes differ in how they respond to marketing messages or other external stimuli. Whereas Prophets are stimulated and increase EB when compelled to, Wizards react negatively resulting in decreased environmental behavior. Psychological reactance moderates the mediated effect of compulsion by magnifying the effect of this path. We propose that higher levels of reactance increase the positive impact of compulsion on Prophets while amplifying the negative effect of compulsion for Wizards. Exposing Wizards to marketing communications compelling environmentalism suppresses their EB.